Organic carbon storage in mountain river valley bottoms of the western United States - Scott, Daniel N., author; Wohl, Ellen, advisor; Covino, Tim, committee member; Nelson, Peter, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2018)
Valley bottoms, which include river channels and associated floodplains, are important components of the terrestrial carbon sink. Downed wood and floodplain soil in valley bottoms act as transient pools of organic carbon (OC) that can be stored for up to millennial timescales. This dissertation focuses on quantifying OC storage as downed wood and soil in mountain river valley bottoms in four disparate watersheds that span three mountain ranges across the western United States. Across these four basins, I measured wood load, floodplain OC content, morphologic metrics, and/or vegetation metrics at a total of 178 sites. I find that wood load is a function of metrics that relate to river corridor spatial heterogeneity and wood storage patterns (together determining wood trapping efficiency) at the reach scale and, at a broader spatial scale, wood supply. Wood in an undisturbed basin stores twice as much wood OC as a similar but extensively clearcut basin. In examining floodplain soil OC, I find that much of the variability in OC concentration is due to local factors, such as soil moisture, elevation (a proxy for temperature), and valley bottom geometry. From this, I conclude that local factors likely play a dominant role in regulating OC concentration in valley bottoms, and that inter-basin trends in climate or vegetation characteristics may not translate directly to trends in OC storage. I also use analysis of OC concentration and soil texture by depth to infer that OC is input to floodplain soils mainly by decaying vegetation, not overbank deposition of fine, OC-bearing sediment. Valley bottoms store significant OC stocks in floodplain soil and downed wood (ranging from 0 to 998 Mg C/ha) that vary with valley bottom form and geomorphic processes. Valley bottom morphology, soil retention, and vegetation dynamics determine partitioning of valley bottom OC between soil and wood, implying that modern biogeomorphic process and the legacy of past erosion regulate the modern distribution of OC in river networks. Soil burial is essential to preserving old OC, as measured by an extensive sample of 121 radiocarbon ages of floodplain soil OC. These radiocarbon data indicate a median residence time of floodplain soil OC of 185 yr BP. The age of the floodplain soil OC pool and the distribution of OC between wood and soil imply that OC storage in mountain rivers is sensitive over relatively short timescales to alterations in soil and wood retention, which may have both short- and long-term feedbacks with the distribution of OC between the land and atmosphere. Mountain river valley bottoms act as a high magnitude and moderately long-lasting pool of OC stored on land.